Development of Collaborative Learning Models in Improving Student Social Skills In Biology Science - Geterudis Kerans; Khristoforus Palli Ngongo (Postgraduate, University of Mataram, 2021)
This study aims to improve students' social skills through a collaborative learning model in Basic Biology courses. This is a research and development (R&D) study. This research consists of six stages, namely: (1) a preliminary study which is evaluative and explorative in nature toward the previous learning model, (2) designing a conceptual model, (3) validating the model, (4) testing the conceptual model, (5) ) revising the results of trials model in order to obtain a final model, and (6) composing the research reports. The development of a collaborative learning model can improve students' social skills. The increasing of students’ social skills can be seen from the skills of students while working in groups, respecting each other's opinions, helping each other in completing assignments and reminding each other in making notes in each other's books and the distribution of tasks during presentations so that each group member has the opportunity to speak